Pengaruh Daya Tarik Iklan Melalui Instagram Dan Minat Beli Terhadap Keputusan Pembelian Pada Luar Garis Coffee Shop - Fernando; Winda Evyanto (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2023)
This study aims to analyze the effect of advertising appeal via Instagram and purchase intention on purchasing decisions at the Outline coffee shop. This type of descriptive research with a quantitative approach will be used in this study. The population can consist of 377 consumers at the Outline coffee shop based on sales data in December 2022. The number of samples selected as respondents in this study was adjusted to 194 respondents from the calculation of the Slovin formula. The analytical method can be used to examine the relationship between these variables by testing data quality tests, classical assumption tests, influence tests and hypothesis testing. The findings of multiple linear regression analysis revealed that the attractiveness of the advertisement contributed to an increase of 35.0% on the purchase decision. Buying interest contributes an increase of 41.9% to purchasing decisions. The analysis of the coefficient of determination (R2) reveals that purchasing decisions at the Outline coffee shop can be explained by the attractiveness of advertisements via Instagram and buying interest at a percentage of 70.6%. The findings of hypothesis testing have shown that the attractiveness of advertising via Instagram and purchase intention have a positive and significant effect partially and simultaneously on purchasing decisions at the Outline coffee shop